Defining severe traumatic brain injury readmission rates and reasons in a rural state. Issue 1 (8th September 2018) - Gardner, James; Sexton, Kevin W; Taylor, John; Beck, William; Kimbrough, Mary Katherine; Davis, Ben; Bhavaraju, Avi; Karim, Saleema; Porter, Austin
Abstract : Background: Readmissions after a traumatic brain injury (TBI) have significant impact on long-term patient outcomes through interruption of rehabilitation. This study examined readmissions in a rural population, hypothesizing that readmitted patients after TBI will be older and have more comorbidities than those not readmitted. Methods: Discharge data on all patients 15 years and older who were admitted to an Arkansas-based hospital for TBI were obtained from the Arkansas Hospital Discharge Data System from 2010 to 2014. This data set includes diagnoses (principal discharge diagnosis, up to 3 external cause of injury codes, 18 diagnosis codes using the International Classification of Disease, 9th Edition, Clinical Modifications), age, gender, and inpatient costs. Hospital Cost and Utilization Project Clinical Classification and Chronic Condition Indicator were used to identify chronic disease and body systems affected in principal diagnosis. Results: Of the 3114 cases of significant head trauma, more than two-thirds were attributed to fall injuries, with motor vehicle crashes accounting for 20% of the remainder. The mean length of stay was 6.5 days. 691 of these patients were admitted to an Arkansas hospital in the following year, totaling 1368 readmissions. Of the readmissions, 16.4% of patients were admitted for altered mental status, 12.9% with shortness of breath (SOB), and 9.4% with chest pain. Mental disorders (psychosis, dementia, and depression) and organic nervous symptoms (Alzheimer's disease, encephalopathy, and epilepsy) were the primary source of readmissions. More than one-third of the patients were admitted in the following year for chronic diseases such as heart failure (8.6%), psychosis (5.2%), and cerebral artery occlusion (4.1%). Discussion: This study showed that there is a significant rate of readmissions in the year after a diagnosis of TBI. Complications with existing chronic diseases are among the most reported reasons for admission in this time period, demonstrating the effect severe head trauma has on long-term treatment. Level of evidence: Level IV, Retrospective epidemiological study.